2018
DOI: 10.1093/jee/toy157
|View full text |Cite
|
Sign up to set email alerts
|

Aphids (Homoptera: Aphididae) on Winter Wheat: Predicting Maximum Abundance of Metopolophium dirhodum

Abstract: In Central Europe, the most abundant aphid infesting the leaves of small grain cereals is Metopolophium dirhodum (Walker) (Homoptera: Aphididae). Annual variation in its seasonal dynamics was evaluated using a 25-yr series of standardized weekly censuses of winter wheat plots. M. dirhodum made up >50 % of the aphids on the foliage. Date of immigration (8 May–3 July), length of period of population increase (0–9 wk), and date of attaining maximum abundance (28 May–22 July) varied greatly. For the prediction, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 38 publications
1
43
0
3
Order By: Relevance
“…From late spring to fall, additional species were present, including the parasitoids Aphidius ervi Haliday and Aphidius avenae Haliday (Krespi, 1990;Krespi et al, 1997;Rabasse et al, 1983) and the aphid Metopolophium dirhodum (Walker). These seasonal variations in aphid and parasitoid species occurrence seem to be consistent across Western Europe in cereal crops (Honek et al, 2018;Lumbierres et al, 2007) and reflect thermal niche separation Le Lann et al, 2011). Aphidius avenae parasitoid shows less cold resistance and more heat resistance than A. rhopalosiphi (Le Lann et al, 2011), while the aphid R. padi prefers cooler conditions and is more cold resistant than S. avenae Jarošík et al, 2003;van Baaren et al, 2010).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…From late spring to fall, additional species were present, including the parasitoids Aphidius ervi Haliday and Aphidius avenae Haliday (Krespi, 1990;Krespi et al, 1997;Rabasse et al, 1983) and the aphid Metopolophium dirhodum (Walker). These seasonal variations in aphid and parasitoid species occurrence seem to be consistent across Western Europe in cereal crops (Honek et al, 2018;Lumbierres et al, 2007) and reflect thermal niche separation Le Lann et al, 2011). Aphidius avenae parasitoid shows less cold resistance and more heat resistance than A. rhopalosiphi (Le Lann et al, 2011), while the aphid R. padi prefers cooler conditions and is more cold resistant than S. avenae Jarošík et al, 2003;van Baaren et al, 2010).…”
Section: Introductionmentioning
confidence: 57%
“…The importance of host species in shaping parasitoid response to climate warming must therefore be accounted (Barton and Ives, 2014). Parasitoids and their hosts may also be influenced by microclimatic refuges in the landscape Tougeron et al, 2016), by surrounding plant covers (Damien et al, 2017;Gagic et al, 2012) or by plant quality (Honek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that both mean minimal temperatures and mean duration of frost events over the winter are predictors of winter aphid abundances and of their variation in occurrence among years. Honek et al (2018) also demonstrated that temperature in winter was an important predictor of maximum abundances of cereal aphids during the weeks following sampling. However, change in mean minimal temperature and duration of frost events only slightly contributed to the trend observed in parasitoid relative abundance changes over the years.…”
Section: Discussionmentioning
confidence: 83%
“…From late spring to fall, additional species were present, including the parasitoids Aphidius ervi Haliday and Aphidius avenae Haliday and the aphid Metopolophium dirhodum (Walker) (Rabasse et al, 1983;Krespi, 1990;Krespi et al, 1997). These seasonal variations in aphid and parasitoid species occurrence seem to be consistent across Western Europe in cereal crops (Lumbierres et al, 2007;Honek et al, 2018) and likely reflect thermal niche separation (Le Lann et al, 2011;Andrade et al, 2016). The parasitoid A. avenae shows less cold resistance and more heat resistance than A. rhopalosiphi (Le Lann et al, 2011), while the aphid R. padi prefers cooler conditions and is more cold resistant than S. avenae (Jarošík et al, 2003;van Baaren et al, 2010;Alford et al, 2016).…”
Section: Introductionmentioning
confidence: 81%